Social and geographical research of the trading sphere of Kharkiv region based on indicators of system development - Кобилін, Павло (Human Geography Journal, 2016)
The article characterizes population trading service in Kharkiv region. The brief analysis of the previous human-geographical research on trading sector was given. The system approach in human geography was emphasized, the research is based on this approach. The definition of “social and geographical system” was given. The essence of the social and geographical system local classifications was revealed. They include indicators of system development (indexes sum of the social and geographical system statistical parameters; projection square of the social and geographical system state in the multidimensional space on plane (by the graph-analytical method), development uniformity; information entropy, given information entropy) and development dynamic – trajectory parameters (cosine of an angle between social and geographical system trajectory and optimal trajectory; distance traveled by a social and geographical system in the multidimensional feature space (L); distance between the current point and the minimal development point (coordinates beginning) (L0); distance from the current point to the maximum development point (end point) (L1); progress coefficient). Among cities of regional subordination the city ofKharkivis highlighted by system development indicators, since it is the biggest city in the region, characterized the highest level of socio-economic development. Among Kharkiv region’s district the highest values of system development have Kharkivs’kyy, Krasnohrads’kyy, Derhachivs’kyy districts, the lowest – Kupyans’kyy, Krasnohrads’kyy, Kolomats’kyy districts. Districts with the relatively high level of social and economic development have higher polygon square, indexes sum, information entropy, given information entropy. The farthest districts, with the relatively low level of social and economic development are characterized lower parameters.